Effect of dexmedetomidine on dynamic cerebral autoregulation and carbon dioxide reactivity during sevoflurane anesthesia in healthy patients - Sujoy Banik (Korean Journal of Anesthesiology, 2020)
Background There are conflicting opinions on the effect of dexmedetomidine on cerebral autoregulation. This study assessed its effect on dynamic cerebral autoregulation (dCA) using a transcranial Doppler (TCD). Methods Thirty American Society of Anesthesiologists physical status I and II patients between 18 and 60 years, who underwent lumbar spine surgery, received infusions of dexmedetomidine (Group D) or normal saline (Group C), followed by anesthesia with propofol and fentanyl, and maintenance with oxygen, nitrous oxide and sevoflurane. After five minutes of normocapnic ventilation and stable bispectral index value (BIS) of 40–50, the right middle cerebral artery flow velocity (MCAFV) was recorded with TCD. The transient hyperemic response (THR) test was performed by compressing the right common carotid artery for 5–7 seconds. The lungs were hyperventilated to test carbon dioxide (CO2) reactivity. Hemodynamic parameters, arterial CO2 tension, pulse oximetry (SpO2), MCAFV and BIS were measured before and after hyperventilation. Dexmedetomidine infusion was discontinued ten minutes before skin-closure. Time to recovery and extubation, modified Aldrete score, and emergence agitation were recorded. Results Demographic parameters, durations of surgery and anesthesia, THR ratio (Group D: 1.26 ± 0.11 vs. Group C: 1.23 ± 0.04; P = 0.357), relative CO2 reactivity (Group D: 1.19 ± 0.34 %/mmHg vs. Group C: 1.23 ± 0.25 %/mmHg; P = 0.547), blood pressure, SpO2, BIS, MCAFV, time to recovery, time to extubation and modified Aldrete scores were comparable. Conclusions Dexmedetomidine administration does not impair dCA and CO2 reactivity in patients undergoing spine surgery under sevoflurane anesthesia.